Carob powder as cocoa substitute in milk and dark compound chocolate formulation - Akdeniz, Esra; Yakisik, Elif; Rasouli Pirouzian, Haniyeh; Akkin, Sedef; Turan, Busra; Tipigil, Ece; Toker, Omer Said; Ozcan, Ozge (SPRINGER INDIA, 2021)
In the current research, the possibility of using carob powder as a substitute for cocoa powder in milk and dark compound chocolates was investigated. Five chocolate samples containing carob powder (20, 40, 60, 80 and 100%) along with control were produced and the physico-chemical analyzes were measured. Chocolate samples were assessed for sensory acceptance by a hedonic scale. The outcomes indicated that chocolate formulations with lower content of carob powder presented higher quality in terms of color parameters, mean particle size and hardness (values close to control). The addition of carob powder resulted in decreased yield stress in dark chocolates. Also dark chocolate formulations containing high levels of carob powder recorded Casson viscosity values similar to control. Moreover, the milk chocolates containing 40% carob powder illustrated no significant differences in sensory properties with control. However acceptance of the dark chocolate samples was similar to control in all attributes. The results proved that it is possible to utilize carob powder to replace cocoa powder in chocolate production in order to improve nutritional values (higher fiber and fewer calories) with agreeable sensory attributes.
Keywords: Carob powder; Chocolate; Substitute; Sensory attributes; Casson viscosity; DIFFERENT BULKING AGENTS; CERATONIA-SILIQUA L.; PODS; QUALITIES; PROFILE; CAKES; FLOUR; WILD; Food Science & Technology